Sistem Pendistribusian Telur berbasis Android Membantu Efisiensi Kerja Karyawan Peternakan - Alanshari, Muhajir; Ardiani, Farida (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
Problems in egg distribution management that still use manual methods, such as recording on paper, present a number of significant obstacles. This process is prone to recording errors, data loss, and requires a lot of time and effort. The main challenges faced are efficiency and accuracy in distribution management. As a solution, the development of a special mobile application is proposed to automate various aspects of egg distribution. This application is designed to simplify the process of recording, storing, and managing data digitally, so that it can overcome the limitations of manual methods. By presenting features such as viewing egg distribution locations, and real-time transaction recording. This application aims to improve operational efficiency, minimize human error, and accelerate distribution. In addition, the implementation of this mobile technology has the potential to have a positive impact on logistics management and customer service quality. With digital transformation in the distribution system, it is expected that there will be a significant increase in productivity and reliability of operational processes. Keywords: egg distribution, manual system, mobile application, efficiency, digital technology